Validation of the Chronic Liver Disease Questionnaire for MASH (CLDQ-MASH) - Zobair M. Younossi; Maria Stepanova; Issah Younossi; Andrei Racila (JHEP Reports)
Background & Aims: The new nomenclature for metabolic dysfunction-associated steatohepatitis (MASH) requires presence of steatohepatitis in the context of at least one cardiometabolic risk. Having a health-related quality of life (HRQL) instrument validated specifically in patients with MASH is important for clinical research and clinical trials. Methods: From our non-alcoholic fatty liver disease/non-alcoholic steatohepatitis (NAFLD/NASH) database, patients who met the definition of MASH according to the new criteria were selected. Subjects had completed the Chronic Liver Disease Questionnaire for NAFLD/NASH (CLDQ-NAFLD/NASH) and other HRQL instruments (Functional Assessment of Chronic Illness Therapy – Fatigue [FACIT-F], Short-Form 36 [SF-36]), and had available clinico-laboratory data including fibrosis non-invasive tests (NITs). The CLDQ-MASH was developed following a standard pipeline and subsequently validated in a non-overlapping sample. Results: There were 4,213 MASH patients included: age 56 ± 11 years, 44% male, 65% type 2 diabetes, 69% advanced fibrosis (F3–F4). The patients with MASH were split 1:2 into a training set used for development of CLDQ-MASH and a testing set used for validation using standard pipeline. After item reduction and exploratory factor analysis with the training set (>90% variance), the CLDQ-MASH contained 35 items and seven domains. With the non-overlapping testing set, CLDQ-MASH demonstrated excellent face validity, internal consistency (all Cronbach’s alpha >0.78), and high correlations with relevant domains of SF-36, FACIT-F (p <0.01). Known-groups validity assessment confirmed that CLDQ-MASH can discriminate patients based on liver disease severity (histology- and NIT-based) and the presence of non-hepatic comorbidities (obesity, type 2 diabetes, depression, clinically overt fatigue, insomnia). In a subsample of subjects with 1-year follow-up, the instrument was responsive to changes in Enhanced Liver Fibrosis® scores and liver stiffness measurements (p <0.05 for four to six domains). Conclusions: The CLDQ-MASH can be used as a valid disease-specific HRQL instrument for patients with MASH. Impact and implications:: The new criteria for metabolic dysfunction-associated steatohepatitis (MASH) are different from those previously used for non-alcoholic steatohepatitis so the evidence collected for the previous criteria need to be revisited, including disease-specific instruments for assessment of health-related quality of life. In patients with MASH, Chronic Liver Disease Questionnaire-MASH (CLDQ-MASH; 35 items, seven domains) has excellent psychometric properties including its internal consistency and various aspects of validity, and is responsive to changes in liver disease severity indicators. The CLDQ-MASH can be used as a valid disease-specific health-related quality of life instrument for MASH in clinical research and clinical trials.